The isolation of alkaloid from the leaves of Samanea saman (Jacq.) Merr. (Leguminosae) - Carluen, Abelen B.; Castillo, Amorita V.; Concepcion. Adoracion B. (Quezon City: College of Pharmacy, University of the Philippines, 1979.)
An alkaloid was isolated from the leaves of Samanea saman (Jacq.) Merr. (Leguminosae) or acacia leaves which were obtained from UP Diliman Campus. The alkaloid was extracted with chloroform. The chloroform extracts were chromatographed on different solvent systems, one of which was butanol-acetic acid-water or BAW with the ratio of 3:1:1.
The isolated compound has a maximum absorbance at 246 nm, ash content of 44% and moisture content of 15-16%.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, March 1979.
Keywords: Alkaloids; Legumes; Acacia